MUNAWIR SYADZALI (SEJARAH PEMIKIRAN DAN KONTRIBUSINYA BAGI PERKEMBANGAN PEMIKIRAN ISLAM INDONESIA KONTEMPORER) - Syahril, Sulthan (Analisis: Jurnal Studi Keislaman, 2011)
This article  discusses  the prominency  of Munawir  Sjadzali  and his thoughts in the vast forest of Indonesia’s contemporary  Islamic legal thoughts.  He  was  widely  famous  for  the  opinion  and  thoughts  he offered  suddenly  interested  public  spotlight.  Indeed,  controversies over his thoughts  took places and inevitably  came about. However, the building concept of the Re-actualization  of (Law) of Islam which is geneanologically  “derivative” of his thought remains a major leap forward  ideas  for  grounding  Islamic  values  of  the  archipelago  on earth, so that Islam is not only known as “Arab”. Islam is a universal religion that is not monopolized by one group of people (Arabs), but each (Muslim) is entitled and has the legitimate right to believe and practice what one believed to be true despite the teachings of Islam they are believing and performing look different from a similar practice in the other hemisphere. Therefore, the reform of tenets (law) of Islam according  to the socio-historical  background  is a sunnatullah.  The main points of this paper is focused on introducing the prominency of Munawir Sjadzali and his thoughts, then the explanation expanded to look at the socio-political background in which he gave rise his views. The study concludes  with a historical  analysis in the light of tarikh tasyri‘ as the first base of Munawir  Sjadzali’s  full flaged views and thoughts.